Development of Youtube integrated google classroom based e-learning media for the light-weight vehicle engineering vocational high school - Willy Prastiyo; As'ari Djohar; P Purnawan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
The purpose of this research is to produce the e-learning media for the Light-Weight Vehicle Chassis and Powertrain Maintenance Subject. The type of this research is the research and development. The procedure applied in this research is the ADDIE model. Construct testing by the expert is done by curriculum expert, practitioner and teaching media expert. Construct testing and content testing were also conducted to 23 students as the user. Qualitative data were analyzed using an iterative step that is reading/memoing, describing, and classifying. Quantitative data were analyzed with descriptive statistics. The research result shows that YouTube Integrated Google Classroom Based E-Learning Media has been produced and tested for Light-Weight Vehicle Chassis and Powertrain Maintenance subjects. The construct testing shows that this e-learning media is decent based on an expert's judgment, and based on the user response shows that the reliability of the construct is good. The content testing shows that students who use the YouTube Integrated Google Classroom Based E-Learning Media have significantly greater learning outcomes compared with students who use the internet to access the website without control.